Evolution of non-expected utility preferences - Widekind, Sven von (Lecture notes in economics and mathematical systems, 2008)
The theory on the evolution of preferences deals with the endogenous formation of preference relations in strategic situations. It is related to the field of evolutionary game theory. Models are based on the 'indirect evolutionary approach' according to which preferences determine choice behavior which in turn determines evolutionary success. The latter eventually governs the evolution of preferences. Literature usually considers a class of preferences which admit an expected utility representation. In this book we analyze the role and the influence of general, possibly non-expected utility pr.